Magnesium- a Forgotten Element: Phenotypic Variation and Genome Wide Association Study in Turkish Common Bean Germplasm - Baloch, Faheem Shehzad; Nadeem, Muhammad Azhar; Sönmez, Ferit; Habyarimana, Ephrem; Mustafa, Zemran; Karaköy, Tolga; Cömertpay, Gönül; Alsaleh, Ahmad; Çiftçi, Vahdettin; Sun, Sangmi; Chung, Gyuhwa; Chung, Yong Suk (Frontiers in Genetics, 2022)
Magnesium (Mg) is the fourth most abundant element in human body and play a role of cofactor for more than 300 enzymatic reactions. In plants, Mg involved in various key physiological and biochemical processes like growth and development, photophosphorylation, chlorophyll formation, protein synthesis and resistance to biotic and abiotic stresses. Keeping in view the importance of this element, present investigation aimed to investigate the Mg contents diversity in the seeds of Turkish common bean germplasm and to identify the genomic regions associated with this element. A total of 183 common bean accessions collected from 19 provinces of Turkey were used as plant material. Field experiments were conducted according to augmented block design during 2018 at two provinces of Turkey and six commercial cultivars were used as control group. Analysis of variance depicted that Mg concentration among 183 common bean accessions was statistically significant (p < 0.05) within each environment, however genotype x environment interaction was non-significant. Moderate level (0.597895) of heritability was found in this study. Mean Mg contents ranged 0.330-1.520 mg kg-1 for Nigde-Dermasyon and Nigde-Derinkuyu landraces respectively, while mean Mg contents were 0.92 mg kg-1. At provinces level, landraces from Bolu and Bitlis were found rich and poor in seed Mg contents respectively. The cluster constellation plot divided the studied germplasm into two populations on the basis of their Mg contents. Marker-trait association was performed using mixed linear model (Q+K) with a total of 7900 DArTseq markers. A total of six markers present on various chromosomes (two at Pv01, and one marker at each chromosome i.e. Pv03, Pv07, Pv08, Pv11) showed statistically significant association for seed Mg contents. DArT-3367607 marker contributed maximum phenotypic variation (7.5%). Additionally, this marker was found within a narrow region of previously reported markers. We are confident that results of this study will contribute significantly to start common bean breeding activities regarding improved Mg contents.